Heart transplant recipients with confirmed 2019 novel coronavirus infection: The Detroit experience. Issue 12 (1st October 2020) - Al‐Darzi, Waleed; Aurora, Lindsey; Michaels, Alexander; Cowger, Jennifer; Grafton, Gillian; Selektor, Yelena; Tita, Cristina; Hannawi, Bashar; Lanfear, David; Nemeh, Hassan W.; Williams, Celeste T.
Abstract: A chronic immunosuppressed state as in solid organ transplant recipients is a reported risk factor for the novel 2019 coronavirus infection. Patients with a history of orthotopic heart transplant (OHT) at a tertiary care transplant center in Detroit, Michigan were retrospectively reviewed from March until May 2020. Clinical parameters and outcomes of 5 OHT recipients and one combined heart–lung recipient with confirmed SARS‐CoV‐2 were obtained. The cohort was predominately African American males with median age of 59 years (interquartile range, 48.25‐73.25). All patients were classified as having mild–moderate disease; none required intubation or ICU admission with no deaths. The most common presenting symptoms were fever and shortness of breath 83% (n = 5), followed by cough and chills 67% (n = 4). All admitted patients (n = 5) received hydroxychloroquine and 3 received high‐dose steroids. Antimetabolites were held for 2 patients (33.3%). The calcineurin inhibitor trough goal was decreased in only 1 patient; 3 other patients, without change in goal, required calcineurin inhibitor dosage reduction. Two patients requiring readmission presented 7 and 23 days after initial symptoms onset. In conclusion, our experience with OHT patients infected by the SARS‐CoV‐2 virus did not have an elevated risk of severe infection. Impact of modifying immunosuppression remains unclear.